The Entrepreneurial Ladder and its Determinants - Peter van der Zwan; Roy Thurik; Isabel Grilo (Tinbergen Institute, 2006)
We test a new model where the entrepreneurial decision is described as a process of successive engagement levels, i.e., as an entrepreneurial ladder. Five levels are distinguished using nearly 12,000 observations from the 2004 “Flash Eurobarometer survey on Entrepreneurship” covering the 25 European Union member states and the United States. The most surprising of the many results is that perception of lack of financial support is no obstacle for moving to a higher entrepreneurial engagement level whereas perceived administrative complexity is a significant obstacle. We also show that the effect of age on the probability of moving forward in the entrepreneurial process becomes negative after a certain age implying that if entrepreneurial engagements are not taken early enough in life they may well never be taken.
Keywords: H10; J23; L26; M13; R12; 330; entrepreneurship; determinants; nascent entrepreneurship; ordered multinomial logit; Europe